Common Transport Policy of the European Union: a Road Map for the Eurasian Economic Union - Y. V. Pak; T. N. Polyanova (Vestnik MGIMO-Universiteta, 2015)
The paper delivers a thorough organizational, economic and institutional analysis of the evolution of common transport policy (CTP) of the European Union (EU). Advanced European experience and practices on the issue are set as an unambiguous territorial and functional benchmark for the breakthrough integration project in the post-soviet space - the Eurasian Economic Union (EEU). When working out its own CTP the EEU faces similar challenges to that of the EU though Eurasian integration offers a unique opportunity to evade European mistakes on its way to creating a modern regional transport and logistics infrastructure at lower costs. The research identifies these failing points in the framework of the European CTP as following: (1) strong reluctance of the member states to surpass economic and political control over the transport industry on to the supranational level, (2) turning of special agencies responsible for the implementation of CTP into an independent actors with political ambitions and (3) inadequate involvement of public-private partnership mechanisms into the regional infrastructure projects. The authors claim a high potential of transport and logistics cooperation within the EEU stressing a pure economic rationale for the introduction of common norms and principles into the industry. Overall, they underline harsh negotiation process and consequently expect tangible results to come solely in the long-term perspective.